Preparation method of antibacterial wear-resistant PE water supply pipe

By using high-density polyethylene, composite fillers, zwitterionic antibacterial microcapsules and other materials, the existing PE water supply pipes are easily prone to bacterial adhesion and wear resistance after long-term use, and long-term antibacterial and excellent wear resistance are achieved.

CN119859336AInactive Publication Date: 2025-04-22HUISUN PIPELINE CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510092325.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-22
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing PE water supply pipes are prone to bacterial and microorganisms to adhere after long-term use, resulting in 'secondary contamination' of water quality, and insufficient wear resistance and overall strength, making it prone to scratches and damage.

Method used

High-density polyethylene, composite filler, zwitterionic antibacterial microcapsules, antioxidants and maleic anhydride grafted polyethylene are used as raw materials, and antibacterial and wear-resistant PE water feed pipe is prepared by heating and mixing and extruding. The composite filler contains modified zinc oxide and cationic copolymer, which enhances the wear resistance and antibacterial properties of the pipe.

Benefits of technology

It realizes the long-term antibacterial properties and excellent wear resistance of PE water supply pipes, significantly reducing bacterial growth and extending the service life of the pipe.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005251923550000121
    Figure BDA0005251923550000121
  • Figure BDA0005251923550000131
    Figure BDA0005251923550000131
  • Figure BDA0005251923550000132
    Figure BDA0005251923550000132
Patent Text Reader

Abstract

The invention discloses a preparation method of an antibacterial wear-resistant PE water supply pipe, and belongs to the field of water supply pipes. The preparation method comprises the following steps: heating the high-density polyethylene to 100-120 DEG C, adding the composite filler, the zwitterionic antibacterial microcapsules, the antioxidant and the compatilizer, stirring and mixing at 130-140 DEG C to obtain a mixture, and performing extrusion molding on the mixture through an extruder to obtain the antibacterial wear-resistant PE water supply pipe. The high-density polyethylene, the composite filler, the zwitterionic antibacterial microcapsule, the antioxidant and the maleic anhydride grafted polyethylene are used as raw materials of the PE water supply pipe, the composite filler effectively enhances the wear resistance of the pipe, and the zwitterionic antibacterial microcapsule is used as a core antibacterial component to endow the pipe with long-acting antibacterial ability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of water supply pipes, and in particular relates to a method for preparing an antibacterial and wear-resistant PE water supply pipe. Background Art

[0002] Water from water plants is distributed to thousands of households through water supply networks. After being disinfected by water plants, water often carries a small amount of microorganisms and organic matter. In the process of flowing through the water supply network, organic matter is not only the nutrition of microorganisms, but also the substance that promotes the formation of biofilm on the inner wall of the network. As the ordinary water supply pipe is used for a longer time, harmful microorganisms will adhere to the inner wall of the pipe and gradually form a stable biofilm. Under the protection of the biofilm, harmful bacteria have stronger drug resistance and stability, causing "secondary pollution" of water quality, becoming one of the main reasons for the decline in water quality in the network, causing serious safety hazards to drinking water, and threatening people's health. In addition, the existing PE water supply pipe has insufficient wear resistance on the outer surface and insufficient overall strength. During the process of moving and transportation, it is easy to be scratched and damaged by external forces, which affects the service life of the pipe.

[0003] Patent CN113621193 B discloses a production process for an anti-aging PE water supply pipe, which is prepared by mixing low-density polyethylene, a coupling agent, a filler, an anti-aging aid, an antioxidant and a lubricant to obtain a mixture, and then preparing the anti-aging PE water supply pipe by granulating and extruding the mixture. The anti-aging PE water supply pipe has good wear resistance and strength, but ignores the safety issues caused by the attachment of bacteria and microorganisms to the PE water supply pipe after long-term use; Patent CN108314819 B discloses an anti-aging and antibacterial PE water supply pipe, which is formed by co-extrusion of an inner layer, a middle layer and an outer layer, wherein the inner layer uses a raw material containing nano zinc oxide, and the outer layer uses a free radical scavenger mixed with Hals622 and Hals944, and the nano zinc oxide has good antibacterial properties, but the invention does not involve the durability characteristics of the antibacterial properties.

[0004] Therefore, providing an antibacterial and wear-resistant PE water supply pipe with excellent antibacterial properties and long-lasting effect is an important issue to be solved in the art. Summary of the invention

[0005] In order to solve the technical problems existing in the prior art, the present invention provides a method for preparing an antibacterial and wear-resistant PE water supply pipe. Specifically, the technical solution of the present invention includes the following contents:

[0006] A method for preparing an antibacterial and wear-resistant PE water supply pipe, the method comprising the following steps:

[0007] After the high-density polyethylene is heated to 100-120° C., composite fillers, zwitterionic antibacterial microcapsules, antioxidants and compatibilizers are added and stirred at 130-140° C. to obtain a mixture, and the mixture is extruded through an extruder to obtain the antibacterial and wear-resistant PE water supply pipe.

[0008] Furthermore, the preparation method of the composite filler comprises the following steps:

[0009] Nano zinc oxide and silane coupling agent G-570 are stirred and reacted to obtain modified zinc oxide. In an inert gas protection environment, methacryloyloxyethyl trimethyl ammonium chloride and modified zinc oxide are mixed and heated to 55-65° C., and then a first initiator is added and stirred and reacted to obtain a cationic copolymer. Montmorillonite, the cationic copolymer and deionized water are stirred and reacted in an environment of 30-50° C. to obtain the composite filler.

[0010] Furthermore, the weight ratio of the nano zinc oxide to the silane coupling agent G-570 is 3:1 to 1.5.

[0011] Furthermore, the weight ratio of the methacryloyloxyethyl trimethylammonium chloride, the modified zinc oxide and the first initiator is 1:1.5-2.5:0.25-0.35.

[0012] Furthermore, the first initiator is ammonium persulfate or sodium bisulfite.

[0013] Furthermore, the weight ratio of the montmorillonite, the cationic polymer and the deionized water is 1:2-3:10-20.

[0014] Furthermore, the method for preparing the zwitterionic antibacterial microcapsules comprises the following steps:

[0015] After N-methyldiethanolamine and N,N-carbonyldiimidazole are stirred and activated at 35-37°C, dimethylaminopropylamine is added in an inert gas protection environment and stirred at 23-25°C to react to obtain an intermediate product; the intermediate product and 1,3-propane sultone are stirred and mixed at 23-25°C, and then the temperature is raised to 60-75°C and stirred to react to obtain a zwitterionic compound; Tween 80 and deionized water are mixed to obtain an aqueous phase, and the zwitterionic compound, silane coupling agent KH-560 and Span 80 are mixed to obtain an oil phase; after the aqueous phase and the oil phase are mixed, a second initiator is added and stirred at 60-80°C to react to obtain the zwitterionic antibacterial microcapsules.

[0016] Furthermore, the weight ratio of the N-methyldiethanolamine, N,N-carbonyldiimidazole and dimethylaminopropylamine is 1:0.6-0.8:0.3-0.5.

[0017] Furthermore, the weight ratio of the intermediate product to 1,3-propane sultone is 1:1 to 2.5.

[0018] Furthermore, the weight ratio of Tween 80 to deionized water is 0.3-0.8:20.

[0019] Furthermore, the weight ratio of the zwitterionic compound, the silane coupling agent KH-560 and Span 80 is 1:4-5:0.2-0.4.

[0020] Furthermore, the weight ratio of the silane coupling agent KH-560 to the second initiator is 1:0.01-0.02.

[0021] Furthermore, the second initiator is potassium persulfate.

[0022] Furthermore, the inert gas is nitrogen or argon.

[0023] Furthermore, the weight ratio of the high-density polyethylene, the composite filler, the zwitterionic antibacterial microcapsules, the antioxidant and the maleic anhydride grafted polyethylene is 40-50:3-5:2-5:0.5-1:1-2.

[0024] Furthermore, the antioxidant is antioxidant 1010, antioxidant 168 or antioxidant 264.

[0025] Furthermore, the die temperature of the extruder is 220-250° C. and the extrusion pressure is 40-50 MPa.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) In the present invention, silane coupling agent G-570 and nano zinc oxide are first reacted to obtain modified zinc oxide, then methacryloyloxyethyl trimethyl ammonium chloride and modified zinc oxide are polymerized to obtain a cationic copolymer, and finally the cationic copolymer is stirred and mixed with montmorillonite to obtain a composite filler. The cationic copolymer molecules in the present invention are rich in quaternary ammonium groups, which can be smoothly intercalated into montmorillonite, effectively improve the original cluster structure of montmorillonite, and significantly improve the dispersibility of montmorillonite. In addition, the longer molecular chains contained in the composite filler can form a stronger physical entanglement with the polyethylene resin molecular chain, effectively improve the interface bonding between the composite filler and polyethylene, so that it has sufficient interface bonding force to fill the gap between the composite filler and the montmorillonite, thereby improving the interface compatibility and enhancing the wear resistance of the PE water supply pipe.

[0028] (2) In the present invention, dimethylaminopropylamine is coupled with N,N-carbonyldiimidazole and N-methyldiethanolamine to obtain an intermediate product, and the intermediate product undergoes a substitution reaction with 1,3-propanesultone to obtain a zwitterionic compound rich in quaternary ammonium groups, and then zwitterionic antibacterial microcapsules are obtained through emulsion polymerization. The zwitterionic antibacterial microcapsules in the present invention are lipophilic, and according to the principle of like dissolves like, the dispersion and interfacial interaction between the zwitterionic antibacterial microcapsules and the polyethylene matrix are enhanced; the zwitterionic antibacterial microcapsules prepared by the present invention have zwitterionic compounds as capsule cores and silicone polymers as capsule walls to form a core-shell microstructure, which enhances the stability of the zwitterionic compounds and achieves slow release and long-lasting antibacterial effects; the antibacterial and wear-resistant PE water supply pipe prepared by the present invention contains zinc oxide and quaternary ammonium groups, which can effectively reduce bacterial growth.

[0029] (3) The PE water supply pipe prepared by the present invention uses high-density polyethylene, composite fillers, zwitterionic antibacterial microcapsules, antioxidants and maleic anhydride grafted polyethylene as raw materials, wherein the composite fillers effectively enhance the wear resistance of the pipe, and the zwitterionic antibacterial microcapsules serve as the core antibacterial component, giving the pipe long-lasting antibacterial ability. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be clearly and completely described below through the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0031] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.

[0032] Preparation Example 1:

[0033] The preparation of the composite filler comprises the following steps:

[0034] 15 parts by weight of nano zinc oxide is dispersed in 150 parts by weight of solvent A (V 去离子水 :V 乙醇 =2:1) ​​ultrasonic dispersion for 25 min to obtain a zinc oxide suspension, 5 parts by weight of silane coupling agent G-570 is dispersed in 100 parts by weight of solvent B (V 去离子水 :V 乙醇=1:1), stirring at a speed of 300r / min and heating to 75°C, then adding 100 parts by weight of zinc oxide suspension, continuing to stir and react for 3h, centrifugally washing and vacuum drying at 60°C for 12h to obtain modified zinc oxide; in a nitrogen protection environment, stirring 10 parts by weight of methacryloyloxyethyl trimethyl ammonium chloride and 15 parts by weight of modified zinc oxide at a speed of 200r / min and heating to 55°C, then adding 0.25 parts by weight of sodium bisulfite, continuing to stir and react for 5h, after the reaction is completed, washing with a mixed solution of ethanol / acetone (volume ratio of 1:1) and vacuum drying at 65°C for 48h to obtain a cationic copolymer; 5 parts by weight of montmorillonite and 10 parts by weight of cationic copolymer are dispersed in 50 parts by weight of deionized water, stirring and reacting at a speed of 400r / min at 30°C for 3h, and vacuum drying at 60°C for 24h to obtain a composite filler.

[0035] Preparation Example 2:

[0036] The preparation of the composite filler comprises the following steps:

[0037] 15 parts by weight of nano zinc oxide is dispersed in 150 parts by weight of solvent A (V 去离子水 : V-=2:1) ultrasonic dispersion for 28 min to obtain zinc oxide suspension, 6 parts by weight of silane coupling agent G-570 is dispersed in 100 parts by weight of solvent B (V 去离子水 :V 乙醇 =1:1), stirring at a speed of 350r / min and heating to 76°C, then adding 100 parts by weight of zinc oxide suspension, continuing to stir and react for 3.2h, centrifugally washing and vacuum drying at 63°C for 14h to obtain modified zinc oxide; in an argon protection environment, stirring 10 parts by weight of methacryloyloxyethyltrimethylammonium chloride and 18 parts by weight of modified zinc oxide at a speed of 300r / min and heating to 58°C, then adding 0.29 parts by weight of ammonium persulfate, continuing to stir and react for 6h, after the reaction is completed, washing with a mixed solution of ethanol / acetone (volume ratio of 1:1) and vacuum drying at 68°C for 52h to obtain a cationic copolymer; 5 parts by weight of montmorillonite and 12 parts by weight of cationic copolymer are dispersed in 70 parts by weight of deionized water, stirring and reacting at a speed of 500r / min at 35°C for 4h, and vacuum drying at 63°C for 28h to obtain a composite filler.

[0038] Preparation Example 3:

[0039] The preparation of the composite filler comprises the following steps:

[0040] 15 parts by weight of nano zinc oxide is dispersed in 150 parts by weight of solvent A (V 去离子水 :V 乙醇=2:1) ​​ultrasonic dispersion for 30 min to obtain a zinc oxide suspension, 5 parts by weight of silane coupling agent G-570 is dispersed in 100 parts by weight of solvent B (V 去离子水 :V 乙醇 =1:1), stirring at a speed of 400r / min and heating to 78°C, then adding 100 parts by weight of zinc oxide suspension, continuing to stir and react for 3.8h, centrifugally washing and vacuum drying at 68°C for 16h to obtain modified zinc oxide; in an argon protection environment, stirring 10 parts by weight of methacryloyloxyethyl trimethyl ammonium chloride and 20 parts by weight of modified zinc oxide at a speed of 350r / min and heating to 60°C, adding 0.32 parts by weight of sodium bisulfite, continuing to stir and react for 6h, after the reaction is completed, washing with a mixed solution of ethanol / acetone (volume ratio of 1:1) and vacuum drying at 72°C for 55h to obtain a cationic copolymer; 5 parts by weight of montmorillonite and 14 parts by weight of cationic copolymer are dispersed in 80 parts by weight of deionized water, stirring and reacting at a speed of 550r / min at 45°C for 4.5h, and vacuum drying at 68°C for 32h to obtain a composite filler.

[0041] Preparation Example 4:

[0042] The preparation of the composite filler comprises the following steps:

[0043] 15 parts by weight of nano zinc oxide is dispersed in 150 parts by weight of solvent A (V 去离子水 :V 乙醇 =2:1) ​​ultrasonic dispersion for 35 min to obtain a zinc oxide suspension, 5 parts by weight of silane coupling agent G-570 was dispersed in 100 parts by weight of solvent B (V 去离子水 :V 乙醇 =1:1), stirring at a speed of 500r / min and heating to 80°C, then adding 100 parts by weight of zinc oxide suspension, continuing to stir and react for 4h, centrifugally washing and vacuum drying at 70°C for 18h to obtain modified zinc oxide; in a nitrogen protection environment, 10 parts by weight of methacryloyloxyethyl trimethyl ammonium chloride and 25 parts by weight of modified zinc oxide are stirred at a speed of 400r / min and heated to 65°C, then adding 0.35 parts by weight of ammonium persulfate, continuing to stir and react for 7h, after the reaction is completed, washing with a mixed solution of ethanol / acetone (volume ratio of 1:1) and vacuum drying at 75°C for 60h to obtain a cationic copolymer; 5 parts by weight of montmorillonite and 15 parts by weight of cationic copolymer are dispersed in 100 parts by weight of deionized water, stirring and reacting at a speed of 600r / min at 50°C for 5h, and vacuum drying at 70°C for 36h to obtain a composite filler.

[0044] Preparation Example 5:

[0045] The preparation of zwitterionic antibacterial microcapsules comprises the following steps:

[0046] Disperse 5 parts by weight of N-methyldiethanolamine and 3 parts by weight of N,N-carbonyldiimidazole in 100 parts by weight of DMSO, stir and activate at 35°C for 1 hour, add 1.5 parts by weight of dimethylaminopropylamine in an argon protection environment, cool to 23°C and stir to react for 24 hours, and after the reaction is completed, dialyze and dry to obtain an intermediate product; disperse 5 parts by weight of the intermediate product and 5 parts by weight of 1,3-propanesulfonate in 100 parts by weight of DMSO, stir and mix at 23°C for 1 hour, heat to 60°C and continue stirring to react for 3 hours, and cool after the reaction is completed. The mixture was cooled to 23°C, filtered and washed to obtain a zwitterionic compound; 0.3 parts by weight of Tween 80 and 20 parts by weight of deionized water were mixed at 30°C for 15 minutes to obtain an aqueous phase; 5 parts by weight of a zwitterionic compound, 20 parts by weight of a silane coupling agent KH-560 and 1 part by weight of Span 80 were mixed at 30°C for 15 minutes to obtain an oil phase; the aqueous phase was added to the oil phase and stirred for 1 hour to obtain a mixture; the mixture was ultrasonically treated for 10 minutes, and 0.2 parts by weight of potassium persulfate was added and stirred at 60°C for 8 hours to obtain zwitterionic antibacterial microcapsules.

[0047] Preparation Example 6:

[0048] The preparation of zwitterionic antibacterial microcapsules comprises the following steps:

[0049] Disperse 5 parts by weight of N-methyldiethanolamine and 3.2 parts by weight of N,N-carbonyldiimidazole in 100 parts by weight of DMSO, stir and activate at 36°C for 1.2 hours, add 1.8 parts by weight of dimethylaminopropylamine in a nitrogen atmosphere, cool to 24°C, stir and react for 25 hours, and after the reaction is completed, dialyze and dry to obtain an intermediate product; disperse 5 parts by weight of the intermediate product and 6 parts by weight of 1,3-propanesulfonate in 100 parts by weight of DMSO, stir and mix at 24°C for 1.5 hours, heat to 70°C, continue stirring and react for 3.5 hours, and after the reaction is completed The mixture was cooled to 24°C, filtered and washed to obtain a zwitterionic compound; 0.6 parts by weight of Tween 80 and 20 parts by weight of deionized water were mixed at 32°C for 18 minutes to obtain an aqueous phase; 5 parts by weight of a zwitterionic compound, 23 parts by weight of a silane coupling agent KH-560 and 1.3 parts by weight of Span 80 were mixed at 32°C for 17 minutes to obtain an oil phase; the aqueous phase was added to the oil phase and stirred for 1.3 hours to obtain a mixture; the mixture was ultrasonically treated for 15 minutes, and 0.23 parts by weight of potassium persulfate was added and stirred at 70°C for 10 hours to obtain zwitterionic antibacterial microcapsules.

[0050] Preparation Example 7:

[0051] The preparation of zwitterionic antibacterial microcapsules comprises the following steps:

[0052] 5 parts by weight of N-methyldiethanolamine and 3.8 parts by weight of N,N-carbonyldiimidazole were dispersed in 100 parts by weight of DMSO, stirred and activated at 36°C for 1.8 hours, and then 2.3 parts by weight of dimethylaminopropylamine were added in an argon protection environment, and the temperature was lowered to 24°C and stirred for reaction for 28 hours. After the reaction, the intermediate product was obtained by dialysis and drying. 5 parts by weight of the intermediate product and 6.5 parts by weight of 1,3-propanesultone were dispersed in 100 parts by weight of DMSO, stirred and mixed at 24°C for 1.5 hours, and then the temperature was raised to 70°C and stirred for reaction for 3.8 hours. After the reaction, the mixture was cooled to 25°C and filtered and washed to obtain a zwitterionic compound. 0.6 parts by weight of Tween 80 and 20 parts by weight of deionized water were mixed at 34°C for 18 minutes to obtain an aqueous phase, 5 parts by weight of a zwitterionic compound, 23 parts by weight of a silane coupling agent KH-560 and 1.8 parts by weight of Span 80 were mixed at 32°C for 18 minutes to obtain an oil phase, the aqueous phase was added to the oil phase and stirred for 1.8 hours to obtain a mixture, the mixture was ultrasonically treated for 25 minutes, 0.35 parts by weight of potassium persulfate was added, and the mixture was stirred at 75°C for 10 hours to obtain zwitterionic antibacterial microcapsules.

[0053] Preparation Example 8:

[0054] The preparation of zwitterionic antibacterial microcapsules comprises the following steps:

[0055] Disperse 5 parts by weight of N-methyldiethanolamine and 4 parts by weight of N,N-carbonyldiimidazole in 100 parts by weight of DMSO, stir and activate at 37°C for 2 hours, add 2.5 parts by weight of dimethylaminopropylamine in a nitrogen atmosphere, cool to 25°C and stir to react for 30 hours, and after the reaction is completed, dialyze and dry to obtain an intermediate product, disperse 5 parts by weight of the intermediate product and 7.5 parts by weight of 1,3-propanesulfonate in 100 parts by weight of DMSO, stir and mix at 25°C for 2 hours, heat to 75°C and continue stirring to react for 4 hours, and cool after the reaction is completed. The mixture was cooled to 25°C, filtered and washed to obtain a zwitterionic compound; 0.8 parts by weight of Tween 80 and 20 parts by weight of deionized water were mixed at 35°C for 20 minutes to obtain an aqueous phase; 5 parts by weight of a zwitterionic compound, 25 parts by weight of a silane coupling agent KH-560 and 2 parts by weight of Span 80 were mixed at 35°C for 20 minutes to obtain an oil phase; the aqueous phase was added to the oil phase and stirred for 2 hours to obtain a mixture; the mixture was ultrasonically treated for 30 minutes, and 0.5 parts by weight of potassium persulfate was added and stirred at 80°C for 12 hours to obtain zwitterionic antibacterial microcapsules.

[0056] Preparation Example 9:

[0057] The preparation of zwitterionic compounds comprises the following steps:

[0058] Disperse 5 parts by weight of N-methyldiethanolamine and 4 parts by weight of N,N-carbonyldiimidazole in 100 parts by weight of DMSO, stir and activate at 37°C for 2 hours, add 2.5 parts by weight of dimethylaminopropylamine in a nitrogen atmosphere, cool to 25°C and stir to react for 30 hours, and after the reaction, dialyze and dry to obtain an intermediate product, disperse 5 parts by weight of the intermediate product and 7.5 parts by weight of 1,3-propanesulfonate in 100 parts by weight of DMSO, stir and mix at 25°C for 2 hours, heat to 75°C and continue stirring to react for 4 hours, and after the reaction, cool to 25°C and filter and wash to obtain a zwitterionic compound.

[0059] Embodiment 1:

[0060] The preparation of antibacterial and wear-resistant PE water supply pipe includes the following steps:

[0061] Add 40 parts by weight of high-density polyethylene into a blender and heat it to 100°C, then add 3 parts by weight of the composite filler prepared in Preparation Example 1, 2 parts by weight of the zwitterionic antibacterial microcapsules prepared in Preparation Example 5, 0.5 parts by weight of antioxidant 1010 and 1 part by weight of maleic anhydride grafted polyethylene, stir and mix at 130°C for 30 minutes, then cool to 40°C to obtain a mixture, and extrude the mixture through an extruder with a die temperature of 220°C and an extrusion pressure of 40 MPa to obtain an antibacterial and wear-resistant PE water pipe.

[0062] Embodiment 2:

[0063] The preparation of antibacterial and wear-resistant PE water supply pipe includes the following steps:

[0064] 45 parts by weight of high-density polyethylene are added into a blender and heated to 110°C. Then, 3.5 parts by weight of the composite filler prepared in Preparation Example 2, 3 parts by weight of the zwitterionic antibacterial microcapsules prepared in Preparation Example 5, 0.6 parts by weight of antioxidant 168 and 1.3 parts by weight of maleic anhydride grafted polyethylene are added, stirred and mixed in an environment of 132°C for 40 minutes, and then cooled to 43°C to obtain a mixture. The mixture is extruded through an extruder with a die temperature of 230°C and an extrusion pressure of 42 MPa to obtain an antibacterial and wear-resistant PE water pipe.

[0065] Embodiment 3:

[0066] The preparation of antibacterial and wear-resistant PE water supply pipe includes the following steps:

[0067] 48 parts by weight of high-density polyethylene are added into a blender and heated to 115°C. Then, 4.5 parts by weight of the composite filler prepared in Preparation Example 3, 4 parts by weight of the zwitterionic antibacterial microcapsules prepared in Preparation Example 7, 0.8 parts by weight of antioxidant 264 and 1.5 parts by weight of maleic anhydride grafted polyethylene are added, stirred and mixed in an environment of 138°C for 50 minutes, and then cooled to 48°C to obtain a mixture. The mixture is extruded through an extruder with a die temperature of 240°C and an extrusion pressure of 45 MPa to obtain an antibacterial and wear-resistant PE water pipe.

[0068] Embodiment 4:

[0069] The preparation of antibacterial and wear-resistant PE water supply pipe includes the following steps:

[0070] 50 parts by weight of high-density polyethylene are added into a blender and heated to 120°C. Then, 5 parts by weight of the composite filler prepared in Preparation Example 4, 5 parts by weight of the zwitterionic antibacterial microcapsules prepared in Preparation Example 8, 1 part by weight of antioxidant 1010 and 2 parts by weight of maleic anhydride grafted polyethylene are added, stirred and mixed in an environment of 140°C for 60 minutes, and then cooled to 50°C to obtain a mixture. The mixture is extruded through an extruder with the die temperature set at 250°C and the extrusion pressure set at 50 MPa to obtain an antibacterial and wear-resistant PE water pipe.

[0071] Comparative Example 1:

[0072] The preparation of antibacterial and wear-resistant PE water supply pipe includes the following steps:

[0073] 50 parts by weight of high-density polyethylene were added into a blender and heated to 120°C. Then, 5 parts by weight of zwitterionic antibacterial microcapsules prepared in Preparation Example 8, 1 part by weight of antioxidant 1010 and 2 parts by weight of maleic anhydride grafted polyethylene were added, stirred and mixed in an environment of 140°C for 60 minutes, and then cooled to 50°C to obtain a mixture. The mixture was extruded through an extruder with a die temperature of 250°C and an extrusion pressure of 50 MPa to obtain an antibacterial and wear-resistant PE water pipe.

[0074] Comparative Example 2:

[0075] The preparation of antibacterial and wear-resistant PE water supply pipe includes the following steps:

[0076] 50 parts by weight of high-density polyethylene are added into a mixer and heated to 120°C, then 5 parts by weight of the composite filler prepared in Preparation Example 4, 1 part by weight of antioxidant 1010 and 2 parts by weight of maleic anhydride grafted polyethylene are added, stirred and mixed in an environment of 140°C for 60 minutes, and then cooled to 50°C to obtain a mixture, and the mixture is extruded through an extruder with the die temperature set at 250°C and the extrusion pressure set at 50 MPa to obtain an antibacterial and wear-resistant PE water pipe.

[0077] Comparative Example 3:

[0078] The preparation of antibacterial and wear-resistant PE water supply pipe includes the following steps:

[0079] 50 parts by weight of high-density polyethylene are added into a blender and heated to 120°C. Then, 5 parts by weight of prepared montmorillonite, 5 parts by weight of zwitterionic antibacterial microcapsules prepared in Preparation Example 8, 1 part by weight of antioxidant 1010 and 2 parts by weight of maleic anhydride grafted polyethylene are added, stirred and mixed in an environment of 140°C for 60 minutes, and then cooled to 50°C to obtain a mixture. The mixture is extruded through an extruder with a die temperature of 250°C and an extrusion pressure of 50 MPa to obtain an antibacterial and wear-resistant PE water pipe.

[0080] Comparative Example 4:

[0081] The preparation of antibacterial and wear-resistant PE water supply pipe includes the following steps:

[0082] 50 parts by weight of high-density polyethylene are added into a mixer and heated to 120°C. Then, 5 parts by weight of the composite filler prepared in Preparation Example 4, 5 parts by weight of the zwitterionic compound prepared in Preparation Example 9, 1 part by weight of antioxidant 1010 and 2 parts by weight of maleic anhydride grafted polyethylene are added, stirred and mixed in an environment of 140°C for 60 minutes, and then cooled to 50°C to obtain a mixture. The mixture is extruded through an extruder with the die temperature set at 250°C and the extrusion pressure set at 50 MPa to obtain an antibacterial and wear-resistant PE water pipe.

[0083] Test Example 1: Antibacterial Performance Testing

[0084] The antibacterial and wear-resistant PE water supply pipes prepared in Examples 1 to 4 of the present invention and Preparation Examples 1 to 4 were cut open from the center and cut into 5 cm samples. The antibacterial performance and antibacterial durability of the samples were tested according to the method specified in JC / T 939-2004 "Antibacterial Performance of Antibacterial Plastic Pipes for Construction". The durability test was to immerse the samples in a water bath at a temperature of 50±2°C for 16 hours, and then detect their antibacterial performance. The test results are shown in Table 1.

[0085] Table 1. Antibacterial rate before durable immersion treatment

[0086]

[0087] Table 2. Antibacterial rate after durable immersion treatment

[0088]

[0089] The results in Table 1 and Table 2 show that the antibacterial rates of the PE water supply pipes prepared in Comparative Examples 1 to 4 were significantly reduced after the durable immersion treatment, while the antibacterial rates of the PE water supply pipes prepared in Examples 1 to 4 of the present invention against Escherichia coli and Staphylococcus aureus were above 90% before the durable immersion treatment, and after the durable immersion treatment, they still had high antibacterial properties and excellent long-term antibacterial durability.

[0090] Test Example 2: Wear resistance test

[0091] The PE water supply pipes prepared in Examples 1 to 4 of the present invention and the PE water supply pipes prepared in Comparative Examples 1 to 4 were tested for wear resistance. According to the test standard in GB / T 3960-2016 "Test method for sliding friction and wear of plastics", the volume wear of the PE water supply pipes prepared above was tested respectively. The test results are shown in Table 3.

[0092] Table 3. Wear resistance test

[0093]

[0094]

[0095] It can be observed from the test results in Table 3 that the PE water supply pipes prepared in Examples 1 to 4 of the present invention have good wear resistance, while the wear resistance of the PE water supply pipes prepared in Comparative Examples 1 to 4 is inferior to that of Examples 1 to 4.

[0096] The test results in Tables 1 to 3 show that the PE water supply pipes prepared in Examples 1 to 4 not only exhibit good long-term antibacterial properties, but also exhibit excellent wear resistance, which is due to the synergistic cooperation of the composite filler and the zwitterionic antibacterial microcapsules in the present invention. The two cooperate with each other and complement each other, and together give the PE water supply pipes good comprehensive performance.

[0097] The above-described embodiments provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected.

Claims

1. A method for preparing an antibacterial and wear-resistant PE water supply pipe, characterized in that: The preparation method comprises the following steps: After the high-density polyethylene is heated to 100-120° C., composite fillers, zwitterionic antibacterial microcapsules, antioxidants and compatibilizers are added and stirred at 130-140° C. to obtain a mixture, and the mixture is extruded through an extruder to obtain the antibacterial and wear-resistant PE water supply pipe.

2. The method for preparing an antibacterial and wear-resistant PE water supply pipe according to claim 1, characterized in that: The preparation method of the composite filler comprises the following steps: Nano zinc oxide and silane coupling agent G-570 are stirred and reacted to obtain modified zinc oxide. In an inert gas protection environment, methacryloyloxyethyl trimethyl ammonium chloride and modified zinc oxide are mixed and heated to 55-65° C., and then a first initiator is added and stirred and reacted to obtain a cationic copolymer. Montmorillonite, the cationic copolymer and deionized water are stirred and reacted in an environment of 30-50° C. to obtain the composite filler.

3. The method for preparing an antibacterial and wear-resistant PE water supply pipe according to claim 2, characterized in that: The weight ratio of the nano zinc oxide to the silane coupling agent G-570 is 3:1-1.

5.

4. The method for preparing an antibacterial and wear-resistant PE water supply pipe according to claim 2, characterized in that: The weight ratio of the methacryloyloxyethyl trimethylammonium chloride, the modified zinc oxide and the first initiator is 1:1.5-2.5:0.25-0.

35.

5. The method for preparing an antibacterial and wear-resistant PE water supply pipe according to claim 2, characterized in that: The weight ratio of the montmorillonite, the cationic polymer and the deionized water is 1:2-3:10-20.

6. The method for preparing an antibacterial and wear-resistant PE water supply pipe according to claim 1, characterized in that: The method for preparing the zwitterionic antibacterial microcapsules comprises the following steps: After N-methyldiethanolamine and N,N-carbonyldiimidazole are stirred and activated at 35-37°C, dimethylaminopropylamine is added in an inert gas protection environment and stirred at 23-25°C to react to obtain an intermediate product; the intermediate product and 1,3-propane sultone are stirred and mixed at 23-25°C, and then the temperature is raised to 60-75°C and stirred to react to obtain a zwitterionic compound; Tween 80 and deionized water are mixed to obtain an aqueous phase, and the zwitterionic compound, silane coupling agent KH-560 and Span 80 are mixed to obtain an oil phase; after the aqueous phase and the oil phase are mixed, a second initiator is added and stirred at 60-80°C to react to obtain the zwitterionic antibacterial microcapsules.

7. A method for preparing an antibacterial and wear-resistant PE water supply pipe as claimed in claim 6, characterized in that: The weight ratio of the N-methyldiethanolamine, N,N-carbonyldiimidazole and dimethylaminopropylamine is 1:0.6-0.8:0.3-0.

5.

8. The method for preparing an antibacterial and wear-resistant PE water supply pipe according to claim 6, characterized in that: The weight ratio of the intermediate product to 1,3-propane sultone is 1:1-2.

5.

9. The method for preparing an antibacterial and wear-resistant PE water supply pipe according to claim 6, characterized in that: The weight ratio of the silane coupling agent KH-560 to the second initiator is 1:0.01-0.

02.

10. The method for preparing an antibacterial and wear-resistant PE water supply pipe according to claim 1, characterized in that: The weight ratio of the high-density polyethylene, the composite filler, the zwitterionic antibacterial microcapsule, the antioxidant and the maleic anhydride grafted polyethylene is 40-50:3-5:2-5:0.5-1:1-2.

Citation Information

Patent Citations

  • An anti-aging and antibacterial PE water supply pipe

    CN108314819B

  • A manufacturing process for anti-aging PE water supply pipes

    CN113621193B

  • Method for preparing anti-protein-contamination type acrylonitrile-sulfonamide polymer ultrafitration film

    CN101003003A

  • Preparation and application of acrylate-group structural type emulsion

    CN104371056A

  • Selective modifying and flooding agent and preparation method thereof

    CN116854849A